BENTUK, FUNGSI, DAN MAKNA PATUNG RATAPAN IBU KOTA PAYAKUMBUH SUMATRA BARAT - ERIKA AGUSTIANINGSIH, Drs. Ariusmedi, M.Sn., Dra. Jupriani, M.Sn. (Universitas Negeri Padang, 2017)
The purpose of this study was to identify the shape, function and meaning of sculpture lament the capital of West Sumatra Payakumbuh. This type of research is descriptive qualitative research. Sources of data in this study is the statue of Mother expectancy (primary data) and informants, and literature (secondary data). Data collection procedures done through observation, interviews, and documentation. The findings of the research are: 1) The shape of the statue of wailing mothers. 2) The function of sculpture wailing mothers. 3) The meaning of the statue of a mother wailing.Kata kunci: bentuk, fungsi, makna, patung ratapan ibu